PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN EKONOMI DI SMA MUHAMMADIYAH 2 PALEMBANG - Fiarika Dwi Utari; Ikbal Barlian; Deskoni Deskoni (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2018)
This study aims to look at the Influence of Cooperative Learning Teams GamesTournament on Student Learning Outcomes in Subjects Economics at SMA Muhammadiyah 2Palembang. The formulation of the problem, namely “is there an influence of cooperativelearning teams games tournament against student learning outcomes on economic subjects inSMA Muhammadiyah 2 Palembang". The method in this research is the method of associativeresearch. The population in this study were all students of X (tenth) grade of SMAMuhammadiyah 2 Palembang. The sample technique used was cluster random sampling andX.2 with 30 students have selected as a sample. techniques used in data collection were testsand observation. The results were obtained thitung ≥ ttabel, then the hypothesis, Ho is rejected andHa accepted. Then it can be concluded there is significant cooperative learning teams tournament games against student learning outcomes on economic subjects in SMA Muhammadiyah 2 Palembang. Furthermore, the results of student learning in the subjects of Economics at SMA Muhammadiyah 2 Palembang with the implementation of Cooperative Learning Teams Games Tournament based on constraints in the study, suggested that teachers who will implement the type of teams games tournament to keep the attention on students within these divisions both initial group or tournament games groups and guiding students in group discussions.